Patients' experience of decision-making and receiving information during radiation therapy: A qualitative study. (October 2017) - Smith, Sian K.; Nathan, Django; Taylor, Jennifer; Van Gelder, Eleni; Dixon, Ann; Halkett, Georgia K.B.; Milross, Christopher; Dhillon, Haryana M.
Abstract: Purpose: This study aimed to explore: (i) patient perceptions of how they are involved in treatment decisions about radiation therapy; (ii) patient knowledge and understanding of treatment; and (iii) what patients value in their interactions with the radiation therapy treatment team. Method: Patients were recruited through radiation oncology departments at metropolitan hospital sites located in Sydney, New South Wales, Australia. Semi-structured interviews were conducted with 21 radiation therapy patients with different types of cancer. Data were analysed using a Framework analysis to compare and contrast patient experiences. Results: Most patients perceived the decision to undergo radiation therapy as agreeing to radiation oncologists recommendations rather than making a choice, but they trusted their radiation oncologist and were happy to follow their advice. Only a few participants reported their radiation oncologist had explained why radiation therapy was recommended, or discussed the benefits and harms. Some participants did not feel prepared for the intensity and disruption of side effects, and conveyed uncertainty about their diagnosis and the potential risk of recurrence. Most patients, irrespective of their type of cancer, valued the treatment team showing a genuine interest in how the treatment was effecting them, and being made to feel part of the department. Conclusion: Greater opportunities are needed to empower patients to ask questions about their uncertainties and concerns. Improvements in these areas will benefit patients and enable them to feel better prepared and know what to expect before and after their treatment. Highlights: Most participants seemed to have difficulties recalling why radiation therapy had been recommended. Feeling part of the department was fundamental to their treatment experience. Many participants were uncertain about how radiation therapy works, its efficacy, and what happens after treatment. Greater opportunities are needed to help patients feel able to seek clarification at different treatment points.